Managing risk using real options in company’s valuation - Kulcsár, Edina (Acta Agraria Debreceniensis, 2014)
The valuation of company is very important because provides information about the current value/situation of company, and through this, provide the opportunity of choosing the best company’s growth alternatives. The future strategic decisions are characterized by lack of knowledge, information, so all measures of company’s growth are closely linked with uncertainty and risk. The company’s valuation process is also related with uncertainty and risk. The risk may result both from the assessed assets and the technique used. In literature, we could find three approaches for risk management: capital budgeting based method, methods based on portfolio analysis and real options approach of risk management. Among them, the real options based methods is the most revolutionary approach for risk management. The advantages of the method, consists in the fact, that the process of establishing strategic decisions integrates the possibility of reversibility, delay and rejections, which isn’t it possible at two previous methods. The method also takes into account the total risk of company, so both the company-specific and systematic risk. In this study, I have used one of the best-known real option based method, the Black-Scholes model, for determining the option’s value. Determination of option value is based on the data of enterprise, which was tested Monte Carlo simulation. One of the basic assumptions of the Black-Scholes model is that the value of option is influenced by several factors. The sensitivity of option’s value could be carried out with so-called “Greeks”.. In the study the sensitivity analysis, was carried out with indicators Delta (Δ), Gamma (Γ) and Vega (ν). The real options based risk management determinations were performed in the R-statistics software system, and the used modules are 'fPortofio' and 'mc2d'. By using of real options method, I have calculated the average value of company capital equal with 38.79 million. By using simulation was carried out 1000 runs. The results of this show a relatively low standard deviation, small interquartile range and normal distribution. In the calculation of indicator Delta, could be concluded the value of company moves in 0.831 proportion to the price of options, the standard deviations of index is low, so the real option based method could be used with success in company’s value estimation. The Gamma index shows the enterprise value is sensitive just for large changes. The result of Vega reflects the value of option, so the company’s value volatility, which is small in this case, but this means a volatility of value. In summary, we can conclude that the call options pricing model, well suited for the determination of company’s value.